The influence of natural environment in residential areas on subjective well-being of the elderly - Li, Zhen; Jiang, Yi; Jin, Ziyang; Pu, Yiran; Li, Hao (Frontiers in Public Health, 2023)
Objectives: The aim of this study is to explore the relationship between the natural environment of residential areas and the subjective well-being of the elderly and the role of elderly's evaluation of the government's environmental protection work in both. Methods: Based on the China Social Survey Database in 2013, 2015, 2017, 2019, Stata were used to process the data screened according to the restricted conditions. Ordered Probit Model and Sobel were used to test the effect relationship among the variables. Results: The subjective well-being of the elderly is roughly increasing. The natural environment of the living area has a significant positive effect on the subjective well-being of the elderly. The evaluation of the elderly on the government's environmental protection work has a positive impact on the elderly's subjective well-being similarly and plays an increasingly important intermediary role in the impact of the natural environment in the residential area on the elderly's subjective well-being. Conclusion: To improve the subjective well-being of the elderly, the government should continue to play a leading role in coordinating environmental protection and pollution control, strengthen publicity of environmental protection work. Moreover improve the residential environment governance and protection system oriented by the elderly's evaluation of the government's environmental protection work.